Method for controlling crystallization of BHJ mixed film PCBM and application of BHJ mixed film PCBM in electronic device

By preparing PCBM with different nano -structures, it is difficult to control the problem of aggregation and crystallization processes in the BHJ hybrid film in the existing technology, realize efficient nano -scale crystal control, and improve the performance of electronic devices.

CN119384199APending Publication Date: 2025-01-28NINGBO INST OF TECH ZHEJIANG UNIV ZHEJIANG
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411313478.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-20
Publication Date
2025-01-28

AI Technical Summary

Technical Problem

The prior art is difficult to effectively control the aggregation and crystallization process of fullerene materials in BHJ hybrid films, especially PCBM materials, resulting in a degradation of device performance.

Method used

By preparing PCBM with different nano -structures, including rotation and annealing treatment to form a Crystal PCBM seed layer, combined with polymer: PCBM hybrid film annealing treatment, and finally removing polymers through solvent washing to obtain the nanogenic PCBM.

Benefits of technology

The nano -scale crystallization control of PCBM in the BHJ hybrid film is achieved, improves the photoelectric conversion efficiency of electronic devices, enhances the crystallization quality of perovskite and reduces non -radiation composite.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119384199A_ABST
    Figure CN119384199A_ABST
Patent Text Reader

Abstract

The invention discloses a method for controlling crystallization of a BHJ mixed film PCBM and application of the BHJ mixed film PCBM in an electronic device. The mixed film comprises one or more polymers. A PCBM hybrid film comprising one or more polymers is deposited on a crystalline fullerene derivative substrate, and the deposited hybrid film is annealed. And exposing the annealed mixed film under ultraviolet light, and cleaning the annealed mixed film with a solvent to obtain the PCBM layer with the nano structure. The fullerene derivative substrate can comprise PCBM, PCBNB, PCBA and the like. The obtained nanostructure PCBM is used as an electron transport layer for preparing a perovskite solar cell, and the photoelectric conversion efficiency of the nanostructure PCBM is far higher than that of a device with TiO2 as the electron transport layer.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of fullerene derivatives, and in particular to a method for controlling the crystallization of a BHJ mixed film PCBM and an application thereof in electronic devices. Background Art

[0002] The crystallization of organic semiconductor materials plays a key role in the performance of electronic devices such as field emission transistors and organic solar cells. Taking organic solar cells as an example, they are usually composed of a layered structure, including a positive electrode, an organic semiconductor active layer, and a negative electrode. Among them, the organic semiconductor bulk heterojunction (BHJ) layer contains n-type (electron acceptor) and p-type (electron donor) semiconductor molecules. In the BHJ layer, the order of organic molecules is closely related to the separation and collection of charges, so it is crucial to effectively control the crystallization of organic semiconductor materials.

[0003] When preparing organic semiconductor films by solution method, the nucleation and crystal growth of organic semiconductors can be induced and controlled by optimizing solvent additives and processing temperature. In addition, amorphous films can be crystallized by post-treatment methods such as thermal annealing and solvent vapor exposure, where the random nucleation process triggers the formation of polycrystalline domains, thereby significantly improving the carrier channel connectivity in the film. However, the preparation of BHJ hybrid films composed of multiple semiconductor materials is more difficult because the crystallization conditions of each material need to be strictly controlled. This challenge includes strictly controlling the crystallization process, the size of the phase separation domains, and the interaction of each material to ensure that the fabricated devices have high performance.

[0004] Fullerene materials play an important role in organic solar cells. However, there is currently no effective method to control the aggregation and crystallization process of fullerenes in BHJ hybrid films. For example, [6,6]-phenyl-C61-butyric acid methyl ester (PCBM) is a commonly used BHJ electron acceptor material, but a PCBM crystallization method suitable for BHJ has not yet been found. Instead, PCBM tends to aggregate and form a pure phase that is phase-separated from the p-type material (such as polymer) in the BHJ. In order to improve the charge separation and collection efficiency, PCBM and other fullerene materials need to be highly crystalline, which can be achieved by increasing the delocalized charge transfer states at the interface or by cascading charge transfer caused by appropriate energy level matching and continuous charge paths.

[0005] Currently, the crystallization of PCBM requires long and rigorous thermal annealing treatments, usually performed above the glass transition temperature of the polymer. However, the crystals grow on a macroscopic scale (approximately 5-50 microns), which results in a significant decrease in device performance due to the reduction of interfaces between materials. Although several methods are known to inhibit the macroscopic crystallization of PCBM, including the use of solvent additives and cross-linking components, effective control of the nucleation and crystal growth of PCBM to form a nanoscale crystalline structure based on BHJ hybrid films has not yet been successfully achieved. Summary of the invention

[0006] In order to solve the above problems, obtain PCBM with different nanostructures, and apply them to the field of electronic devices, the present invention provides a method for controlling the crystallization of PCBM in a BHJ mixed film and its application in electronic devices. Specifically, the present invention is a method for preparing PCBM with different nanostructures, which mainly includes two parts: the first part, the formation of PCBM nanostructures in a BHJ (polymer: PCBM) mixed film; the second part, removing the polymer in the BHJ mixed film to obtain the nanostructured PCBM. By applying the prepared nanostructured PCBM as an electron transport layer in an electronic device, the photoelectric conversion efficiency of the obtained device is improved.

[0007] The object of the present invention is achieved through the following technical solution: a method for controlling the crystallization of a BHJ hybrid film PCBM and its application in electronic devices is provided, the method comprising the following steps:

[0008] (1) preparing a layer of PCBM as a PCBM seed layer by spin coating;

[0009] (2) annealing the spin-coated PCBM seed layer to form a crystalline PCBM seed layer; the annealing temperature range is 140-160° C.;

[0010] (3) preparing a PCBM mixed solution with a mass ratio of organic solar cell semiconductor polymer to PCBM of 1:1-1.5, spin coating and annealing the solution to obtain a PCBM mixed film; and then transferring the solution onto the PCBM seed layer to form a double-layer PCBM / PCBM mixed film;

[0011] (4) annealing the double-layer PCBM / PCBM mixed film at a temperature of 140-160° C. to form a crystalline PCBM mixed film;

[0012] (5) The polymer in the crystalline PCBM mixed film is removed by washing with a solvent, and finally a nanostructured PCBM is obtained.

[0013] A method for controlling the crystallization of BHJ hybrid thin film PCBM is provided, and the nanostructured PCBM prepared is used as an electron transport layer in electronic devices.

[0014] Specifically, the PCBM in step (1) can be replaced by [6,6]-phenyl-C61-butyric acid n-butyl ester (PCBNB), [6,6]-phenyl-C61-butyric acid (PCBA) or other fullerene derivatives.

[0015] Specifically, the semiconductor polymer of the organic solar cell in step (3) includes amorphous PS, crystalline P3HT, semi-crystalline PTB7 and other semiconductor polymers.

[0016] Specifically, the double-layer PCBM / PCBM mixed film in step (4) has a two-layer structure, one layer is a crystallized PCBM, and the other layer is a polymer layer.

[0017] Furthermore, the step (5) includes the following sub-steps:

[0018] (5.1) The obtained crystalline PCBM hybrid film is exposed to ultraviolet light. The sample is 1 cm away from the ultraviolet light. The exposure time is related to the thickness of the film.

[0019] (5.2) Soaking the sample after UV irradiation in acetone solvent for 1-2 minutes to remove the semiconductor polymer of the organic solar cell;

[0020] (5.3) The sample from which the polymer is removed is dried, and the formed nanostructured PCBM can then be observed using a scanning electron microscope (SEM) or an optical microscope.

[0021] Specifically, the thickness of the nanostructured PCBM in step (5) is determined by the thickness of the PCBM mixed film; therefore, the thickness can be controlled by adjusting the concentration of the PCBM mixed solution.

[0022] Specifically, the wavelength range of the ultraviolet light in step (5.1) is 350-400nm.

[0023] Specifically, the shape of the nanostructured PCBM is determined by the structure of the fullerene derivative of the bottom seed layer; when the bottom is the PCBM seed layer, the final product is nanorod PCBM; when the bottom is the PCBA seed layer, the final product is nanowire PCBM.

[0024] The beneficial effects of the present invention are as follows:

[0025] 1) Compared with monolayer TiO2, nanostructured PCBM has higher electron mobility;

[0026] 2) The emergence of nanostructured PCBM can assist perovskite crystallization and improve the quality of perovskite crystallization;

[0027] 3) Nanostructured PCBM can diffuse to the perovskite grain boundaries, reduce defects at the perovskite interface, and reduce non-radiative recombination.

[0028] In addition, the different shapes of nanostructured PCBM will also affect the photovoltaic performance of perovskite solar cells. Compared with the nanowire PCBM electron transport layer, the perovskite solar cell prepared with the nanorod PCBM electron transport layer has better photovoltaic performance. This is mainly because the nanorod PCBM is a mesoporous structure, which can effectively shorten the distance for electrons in the perovskite layer to be transmitted to the electron transport layer, and promote the effective separation and extraction of electrons. BRIEF DESCRIPTION OF THE DRAWINGS

[0029] Figure 1 Schematic diagram of the formation of nanostructured PCBM in the polymer:PCBM mixed film of the present invention;

[0030] Figure 2 Schematic diagram of obtaining nanostructured PCBM by solvent washing in the present invention;

[0031] Figure 3 It is a ratio diagram of the polymer of the present invention and PCBM;

[0032] Figure 4 It is a scanning electron microscope (SEM) image of the present invention;

[0033] Figure 5 The scanning electron microscope (SEM) image of the nanostructured PCBM obtained by using PCBNB and PCBA as the bottom seed layer of the present invention;

[0034] Figure 6 The device structure diagram and JV curve diagram of the perovskite solar cell of the present invention. DETAILED DESCRIPTION

[0035] The object of the present invention is achieved through the following technical solutions:

[0036] Part I: The formation of PCBM nanostructures in polymer:PCBM hybrid films requires four steps:

[0037] (1) Prepare a layer of PCBM (or other fullerene derivatives such as [6,6]-phenyl-C61-butyric acid n-butyl ester (PCBNB), [6,6]-phenyl-C61-butyric acid (PCBA)) as a seed layer by spin coating.

[0038] (2) The spin-coated PCBM layer needs to be annealed at a temperature in the range of 140-160°C to form a crystalline PCBM layer.

[0039] (3) Preparing polymer:PCBM mixed films of different concentrations and different ratios (1:0.5, 1:1, 1:1.5) (i.e., preparing a PCBM mixed solution with a mass ratio of organic solar cell semiconductor polymer to PCBM of 1:1-1.5), and then transferring it onto the PCBM seed layer to form a double-layer PCBM / polymer:PCBM film (i.e., a double-layer PCBM / PCBM mixed film, the double-layer PCBM / PCBM mixed film has a two-layer structure, one layer is crystalline PCBM, and the other layer is a polymer layer). The organic solar cell semiconductor polymer includes amorphous PS, crystalline P3HT, semi-crystalline PTB7 and other semiconductor polymers.

[0040] (4) Annealing the double-layer PCBM / polymer:PCBM film at a temperature of 140-160° C. to form a crystalline film.

[0041] It should be emphasized here that if there is no crystalline PCBM seed layer or an amorphous PCBM seed layer is used, the PCBM in the polymer:PCBM blend film will not crystallize. In addition, the crystallinity of the polymer does not affect the crystallization process of PCBM in the polymer:PCBM blend film. Three different polymers were used here, namely P3HT poly(3-hexylthiophene-2,5-diyl) (crystalline), PTB7 poly({4,8-bis[(2-ethylhexyl)oxy]benzo[1,2-b:4,5-b']disulfan-2,6-diyl}{3-fluoro-2-[(2-ethylhexyl)carbonyl]thieno[3,4-b]thiophenediyl}) (semi-crystalline), and PS polystyrene (amorphous) because they have different crystallization abilities.

[0042] The second part, such as Figure 2 As shown, in order to obtain nanostructured PCBM, the polymer in the polymer:PCBM mixed film needs to be removed by solvent washing. PS is selected as the polymer here. The second part includes three steps:

[0043] (5) The crystalline PCBM mixed film obtained in the first part: the PCBM film is exposed to ultraviolet light (wavelength range 350-400nm), the sample is 1 cm away from the ultraviolet light, and the exposure time is related to the thickness of the film.

[0044] (6) The sample irradiated with UV light is immersed in acetone solvent for 1-2 minutes to remove the polymer PS.

[0045] (7) The sample from which the polymer has been removed is dried, and then a scanning electron microscope (SEM) or an optical microscope is used to observe that a nanostructured PCBM has been formed.

[0046] The size of the nanostructured PCBM observed under a microscope can be controlled by the ratio of polymer to PCBM in the polymer:PCBM mixed film. When the mass ratio of PS:PCBM is 1:0.5, the average size of the nanostructured PCBM is about 150nm. When the mass ratio of PS:PCBM is 1:1, the average size of the nanostructured PCBM is about 300nm. When the mass ratio of PS:PCBM is 1:1.5, the average size of the nanostructured PCBM is about 500nm. The thickness of the nanostructured PCBM is determined by the thickness of the polymer:PCBM mixed film. The thickness can be controlled by adjusting the concentration of the polymer:PCBM mixed solution. The shape of the nanostructured PCBM is determined by the structure of the fullerene derivative of the bottom seed layer. When the bottom is the PCBM seed layer, the final result is nanorod PCBM; when the bottom is the PCBA seed layer, the final result is nanowire PCBM.

[0047] The nanostructured PCBM obtained above has high electron mobility and conductivity, so it can be used as an electron transport layer in perovskite solar cells. We prepared a perovskite solar cell with the structure of FTO / TiO2 / nanostructured PCBM / perovskite / Spiro-OMeTAD / Ag. By comparison, it was found that the photovoltaic device containing nanostructured PCBM has better performance.

[0048] Embodiment 1:

[0049] Characterization of PCBM crystallization in polymer:PCBM blended films

[0050] In order to study the crystallization of PCBM in polymer:PCBM blended films, such as Figure 1 As shown in Figure 2, we used synchrotron radiation to perform two-dimensional GIXRD measurements of the films. The PCBM films obtained by spin coating had a q of 0.75 and The wide ring structure ( Figure 1 a), indicating that it has an isotropic amorphous structure. After annealing at 150 °C, the PCBM film shows a dot-like diffraction pattern, especially at q of 1.38, 1.39 and There is an obvious intensity peak at Figure 1 The presence of multiple peaks with the same q value indicates the presence of multiple PCBM crystal domains with preferred orientation in the film. xy for and The peak at is consistent with the in-plane GIXRD pattern. After transferring the polymer:PCBM layer onto the crystalline PCBM layer, a wide ring, which is caused by the layered structure of the polymer ( Figure 1 c). In addition, the broad rings of amorphous PCBM reappeared because of the presence of aggregated PCBM in the polymer:PCBM layer. After annealing at 150 °C, the intensity of the amorphous PCBM rings decreased, and the diffraction spots of PCBM crystals intensified and slightly broadened, but no new spots appeared ( Figure 1 d). This result indicates that the PCBM in the polymer:PCBM layer crystallized after annealing and its crystal structure and orientation are similar to those of the bottom PCBM seed layer.

[0051] Embodiment 2:

[0052] Characterization of Nanostructured PCBM Morphology

[0053] Scanning electron microscopy (SEM) images were used to study the morphological characteristics of nanostructured PCBM. Figure 3 As shown in Figure 2, nanorod-like PCBM structures were observed. The length of the nanorod PCBM depends on the PS:PCBM mixing ratio in the polymer:PCBM blend film. Figure 3 As shown in (a), when the PCBM ratio is low (PS:PCBM = 1:0.5, mass ratio), nanorod-like structures with a length of about 150 nm are observed. As the PCBM content increases, the average length of the nanorods increases to 300 nm (PS:PCBM = 1:1, Figure 3 (b)) and 500nm (PS:PCBM=1:1.5, Figure 3 (c)). This may be due to the preferential growth of PCBM crystals along the long axis of the nanorods. More PCBM in the polymer:PCBM hybrid film can increase the supply of PCBM molecules to the interface, thereby increasing the size of the crystals. In addition, the SEM images show that the nanorod-like PCBM structure does not have a strong preferred orientation in the thickness direction.

[0054] The thickness of the nanostructured PCBM is determined by the thickness of the polymer:PCBM mixed film. The thickness can be controlled by adjusting the concentration of the polymer:PCBM mixed solution. Figure 4 As shown, Figure 4 (a) The image shows a thinner nanostructured PCBM obtained from a thinner PS:PCBM mixed film (80 nm); Figure 4 (b) shows the thicker nanostructured PCBM obtained from the thicker PS:PCBM mixed film (200nm).

[0055] To investigate the factors that affect the shape of nanostructured PCBM, we selected different fullerene derivatives as the bottom seed layer. PCBNB is similar in structure to PCBM, but has a longer fat tail. After annealing, PCBNB is highly crystalline in the film and is hexagonally tightly packed. Figure 5 As shown (where Figure 5 (a) An optical microscope image of the nanostructured PCBM obtained using PCBNB as the bottom seed layer; Figure 5 (b) The figure shows a scanning electron microscope (SEM) image of the nanostructured PCBM obtained using PCBA as the bottom seed layer; Figure 5 Optical microscopy of (a) shows that the epitaxially grown PCBM forms large hexagonal crystals with a size greater than 100 μm. Using another fullerene derivative PCBA similar to PCBM as the bottom seed layer, the epitaxially grown PCBM is a nanowire structure, such as Figure 5 (b) Therefore, the crystallization behavior of PCBM significantly depends on the structure and orientation of the grains in the seed layer, which indicates the importance of the grains in the seed layer and their influence on the induced crystallization.

[0056] Embodiment 3:

[0057] Perovskite solar cell performance characterization

[0058] like Figure 6 As shown, Figure 6 (a) The figure shows the device structure of a perovskite solar cell; Figure 6 (b) Figure is the JV curve.

[0059] Preparation of perovskite solar cells with the structure of FTO / TiO2 / PCBM nanostructure / perovskite / Spiro-OMeTAD / Ag ( Figure 6 (a)). The JV curve of the perovskite solar cell is shown in Figure 6 As shown in (b), it can be expected that the perovskite solar cells based on nanorod PCBM have higher V OC , FF and PCE. As shown in Table 1, the PCE of the device without PCBM is 9%, V OC =1.00V, J SC 20.92 mA cm -2 , FF is 43%. In contrast, the PCE of the device based on nanorod PCBM increases rapidly to 15.1%, V OC Higher, 1.10V, J SC 22.52 mA cm -2 , FF is 61%. The PCE of the device based on nanowire PCBM is 13%, VOC is 1.08V, J SC 23.09 mA cm -2 , FF is 52%.

[0060] Table 1

[0061]

[0062] The above is only a preferred implementation case of the present invention and does not limit the present invention in any form. Although the implementation process of the present invention is described in detail above, for those familiar with the art, they can still modify the technical solutions recorded in the above examples, or replace some of the technical features therein with equivalents. All modifications, equivalent replacements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for controlling the crystallization of BHJ hybrid film PCBM, characterized in that: The following steps are involved: (1) preparing a layer of PCBM as a PCBM seed layer by spin coating; (2) annealing the spin-coated PCBM seed layer to form a crystalline PCBM seed layer; the annealing temperature range is 140-160° C.; (3) preparing a PCBM mixed solution with a mass ratio of organic solar cell semiconductor polymer to PCBM of 1:1-1.5, spin coating and annealing the solution to obtain a PCBM mixed film; and then transferring the solution onto the PCBM seed layer to form a double-layer PCBM / PCBM mixed film; (4) annealing the double-layer PCBM / PCBM mixed film at a temperature of 140-160° C. to form a crystalline PCBM mixed film; (5) The polymer in the crystalline PCBM mixed film is removed by washing with a solvent, and finally a nanostructured PCBM is obtained.

2. An application of the nanostructured PCBM prepared by the method for controlling the crystallization of BHJ hybrid thin film PCBM as claimed in claim 1 as an electron transport layer in an electronic device.

3. The method for controlling the crystallization of BHJ hybrid thin film PCBM according to claim 1, characterized in that: The PCBM in step (1) can be replaced by [6,6]-phenyl-C61-butyric acid n-butyl ester (PCBNB), [6,6]-phenyl-C61-butyric acid (PCBA) or other fullerene derivatives.

4. The method for controlling the crystallization of BHJ hybrid thin film PCBM according to claim 1, characterized in that: The organic solar cell semiconductor polymer in step (3) includes amorphous PS, crystalline P3HT, semi-crystalline PTB7 and other semiconductor polymers.

5. The method for controlling the crystallization of BHJ hybrid thin film PCBM according to claim 1, characterized in that: The double-layer PCBM / PCBM mixed film in the step (4) has a two-layer structure, one layer is a crystallized PCBM, and the other layer is a polymer layer.

6. The method for controlling the crystallization of BHJ hybrid thin film PCBM according to claim 1, characterized in that: The step (5) comprises the following sub-steps: (5.1) The obtained crystalline PCBM hybrid film is exposed to ultraviolet light. The sample is 1 cm away from the ultraviolet light. The exposure time is related to the thickness of the film. (5.2) Soaking the sample after UV irradiation in acetone solvent for 1-2 minutes to remove the semiconductor polymer of the organic solar cell; (5.3) The sample from which the polymer is removed is dried, and the formed nanostructured PCBM can then be observed using a scanning electron microscope (SEM) or an optical microscope.

7. The method for controlling the crystallization of BHJ hybrid thin film PCBM according to claim 1, characterized in that: The thickness of the nanostructured PCBM in step (5) is determined by the thickness of the PCBM mixed film; therefore, the thickness can be controlled by adjusting the concentration of the PCBM mixed solution.

8. The method for controlling the crystallization of BHJ hybrid thin film PCBM according to claim 1, characterized in that: The wavelength range of the ultraviolet light in the step (5.1) is 350-400nm.

9. The method for controlling the crystallization of BHJ hybrid thin film PCBM according to claim 1, characterized in that: The shape of the nanostructured PCBM is determined by the structure of the fullerene derivative of the bottom seed layer; When the bottom layer is a PCBM seed layer, what is finally obtained is nanorod PCBM; When the bottom layer is a PCBA seed layer, what is finally obtained is nanowire PCBM.